Development of static direct tensile testing method for asphalt mixture at low temperature

The tensile test method for asphalt mixtures addresses the challenge of evaluating low-temperature crack resistance by using a rod-shaped form with specific cross-sectional areas and a formwork unit, providing accurate stress-strain measurements for predicting crack resistance in cold regions.

JP2025017163APending Publication Date: 2025-02-05EAST NIPPON EXPRESSWAY COMPANY LIMITED +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
JP2023120093
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-02-05

AI Technical Summary

Technical Problem

Existing methods fail to accurately predict and evaluate the low-temperature crack resistance of asphalt pavements in cold regions, as conventional tests do not account for the adhesion of the asphalt mixture layer to underlying layers, leading to unreliable stress measurements and difficulty in creating suitable test forms.

Method used

A tensile test method is developed for asphalt mixtures, using a rod-shaped test form with specific cross-sectional areas and parallel portions to measure strain and stress, along with a formwork unit to easily create test specimens, allowing for accurate evaluation of low-temperature crack resistance.

Benefits of technology

The method enables reliable measurement of stress-strain relationships, facilitating the prediction and evaluation of low-temperature crack resistance in asphalt pavements, thereby aiding in material selection and design for cold regions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025017163000001_ABST
    Figure 2025017163000001_ABST
Patent Text Reader

Abstract

To provide a testing method capable of evaluating low-temperature crack resistance of an asphalt pavement.SOLUTION: This testing method applies a tensile load on a sample containing an asphalt mixture to measure distortion and / or stress. The sample is a rod-like sample including a pair of fixed parts in the load axis direction of the tensile load, a parallel part provided between the fixed parts; and a pair of intermediate parts provided between the fixed parts and the parallel part, and formed such that the sectional area of a section perpendicular to the load axis direction in the order of the parallel part, the intermediate parts, and the fixed parts.SELECTED DRAWING: Figure 7
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a tensile test method, and more particularly to a tensile test method for a specimen made of an asphalt mixture, a method for evaluating the low-temperature crack resistance of an asphalt mixture layer using the same, a formwork unit for preparing a specimen made of an asphalt mixture, and a specimen preparation device including the formwork unit. [Background technology]

[0002] In winter, cracks called "low-temperature cracks" may occur in asphalt pavements in cold regions such as Hokkaido. Low-temperature cracks are typically cracks that occur at approximately equal intervals across the road, and are also called low-temperature cracks or temperature stress cracks. When low-temperature cracks occur, they can cause the destruction of the asphalt pavement to progress, or rainwater can seep in through the low-temperature cracks, reducing the bearing capacity of the roadbed and subgrade, leading to the destruction of the asphalt pavement. Therefore, it is very important to properly evaluate the occurrence of low-temperature cracks in cold regions and the low-temperature crack resistance of asphalt pavements applied to cold regions.

[0003] As far as the inventors know, there is no general method for predicting the occurrence of low-temperature cracks or evaluating the low-temperature crack resistance of asphalt pavement. At the research level, for example, Non-Patent Document 1 discloses a method using a compression test, which reports that a correlation was found between the compression strength when a cylindrical specimen taken from a low-temperature crack occurrence site was broken by a tensile stress generated in a direction perpendicular to the compression direction and the amount of low-temperature cracks. However, as seen in Non-Patent Document 2, for example, it has also been reported that the compression strength does not correlate with the frequency of crack occurrence in cold regions, and the current situation is that it is not generally adopted.

[0004] On the other hand, as can be seen in, for example, Non-Patent Document 2, there are reports that the bending strain at the time of bending failure correlates with the frequency of occurrence of low-temperature cracks, but this is not generally adopted at present. In actual pavements, the asphalt mixture layer is firmly adhered to the layers above and below it, and its movement is restricted by its own weight, so it is difficult to imagine that low-temperature cracks would occur due to the deformation assumed in the bending test. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] Kimio Maruyama, Hideto Takemoto, "Study on Various Test Values ​​and Low-Temperature Crack Generation Rate Using Field Cores", 57th Annual Academic Conference of the Japan Society of Civil Engineers, Presentation Date: 2002 / 09 / 25~ 2002 / 09 / 27 [Non-Patent Document 2] Manabu Oguri, Morito Takahashi, Yasuyoshi Ebiko, "Selection of asphalt for suppressing low-temperature cracking", Civil Engineering Research Institute Monthly Report No. 542, July 1998 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made to solve the problems of the prior art as described above, and in one aspect, it is an object of the present invention to provide a test method capable of evaluating the low-temperature crack resistance of asphalt pavement. [Means for solving the problem]

[0007] Conventionally, it has been generally believed that low-temperature cracks occur due to thermal contraction of asphalt pavement exposed to cold climates. However, when we look at asphalt pavement at actual sites, the asphalt mixture layer that constitutes the surface layer of asphalt pavement is firmly attached to the roadbed layer, base layer, and other layers that exist below it, and its movement is restricted. Therefore, it is difficult to think that the asphalt mixture layer that constitutes the surface layer of asphalt pavement is freely contracting due to temperature, as assumed in the conventional thinking, even if it is exposed to cold climates.

[0008] The inventors of the present invention have repeatedly reconsidered the mechanism of cracking of asphalt pavement in cold regions, and came up with the idea that the thermal shrinkage of the asphalt mixture layer exposed to a cold climate is suppressed by the strong adhesion with the subgrade layer and base layer that exist below it, and as a result, tensile stress acts on the asphalt mixture layer in which the thermal shrinkage is suppressed, and this tensile stress is the cause of the low-temperature cracks. Based on this idea, the inventors have come to consider tensile tests on specimens made of asphalt mixture in order to evaluate the tensile strength of the asphalt mixture layer at a test temperature assuming a cold region. However, when the inventors of the present invention prepared a rectangular parallelepiped-shaped specimen made of the asphalt mixture that constitutes the asphalt mixture layer and tried to perform a static tensile test using this, in most cases, the specimen was destroyed by the load of tensile stress near the jig that fixed the specimen, probably because the tensile stress was concentrated near the jig that fixed the specimen, and it was not possible to obtain a stress-strain curve that reflected the characteristics of the asphalt mixture. Moreover, the process of forming a specimen made of asphalt mixture into the required shape for the tensile test required a great deal of effort, which was presumed to be one of the reasons why tensile tests had not been conducted on asphalt mixtures.

[0009] In response to this, the inventors, in the course of further research efforts, discovered that if a rod-shaped specimen is used that is provided with a pair of fixed portions, a parallel portion provided between the pair of fixed portions, and a pair of intermediate portions provided between the pair of fixed portions and the parallel portions, along the longitudinal direction of the specimen, i.e., along the load axis direction of the tensile load, and that is formed so that the cross-sectional areas of the cross sections perpendicular to the load axis direction increase in the order of the parallel portions, the intermediate portions, and the fixed portions, when a tensile load is applied to the specimen, it is possible to more reliably break the specimen near the center of the specimen, i.e., at the parallel portions of the specimen, and thus a stress-strain curve that reflects the characteristics of the asphalt mixture that constitutes the specimen can be more efficiently obtained.

[0010] That is, in one aspect, the present invention provides A tensile test method for obtaining strain and / or stress by applying a tensile load to a specimen made of an asphalt mixture, comprising: The above problem is solved by providing a method characterized in that the specimen is a rod-shaped specimen having, along the load axis direction of the tensile load, a pair of fixed portions, a parallel portion provided between the pair of fixed portions, and a pair of intermediate portions provided between the pair of fixed portions and the parallel portions, and is formed so that the cross-sectional areas of the cross sections perpendicular to the load axis direction increase in the order of the parallel portions, the intermediate portions, and the fixed portions.

[0011] However, as mentioned above, it has not been easy to prepare a specimen made of an asphalt mixture and having a predetermined shape. Because a specimen made of an asphalt mixture is very strong, it takes a lot of time and effort to mold the specimen into a predetermined shape. This can be seen from the fact that most tests for testing the properties of specimens made of asphalt mixtures use specimens with simple shapes, such as cylindrical or rectangular prism shapes.

[0012] In response to this, the present inventors have further intensively researched and found that by using the following formwork unit for preparing a specimen made of an asphalt mixture, a specimen having a predetermined shape, for example, a specimen having the shape described above, can be easily and quickly prepared. That is, in one aspect, the present invention provides a formwork unit for preparing a specimen made of an asphalt mixture, comprising: An inner frame structure formed by combining an inner frame bottom member and an inner frame side member, the inner frame structure having an internal space surrounded by the inner frame bottom member and the inner frame side member, the inner frame structure having a convex portion on a lower surface of the inner frame bottom member; an outer frame structure formed by combining an outer frame bottom member and an outer frame side member, capable of accommodating one or more of the inner frame structures in an internal space surrounded by the outer frame bottom member and the outer frame side member, the outer frame bottom member having one or more through holes that engage with the protrusions of the inner frame structure; As described below, this form unit allows a specimen of a desired shape to be easily and quickly produced by using an inner frame bottom member and an inner frame side member of a predetermined shape and appropriately changing the shape of the internal space surrounded by the inner frame bottom member and the inner frame side member.

[0013] Furthermore, the inventors performed the above-mentioned tensile test method using the thus obtained specimen, measured the breaking strain of the specimen made of the asphalt mixture at a specified test temperature, and compared the measured value with an estimated value of the strain that is thought to occur in the asphalt mixture layer made of the asphalt mixture at a site in a cold region. Surprisingly, the magnitude relationship was in excellent agreement with the low-temperature cracking behavior in cold regions. As a result, the inventors found that it is possible to predict the cracking behavior of asphalt pavement in cold regions based on the breaking strain and / or breaking stress obtained by a static tensile test of the specimen made of the asphalt mixture, in other words, it is possible to evaluate the low-temperature cracking resistance of the asphalt mixture layer.

[0014] That is, in one aspect, the present invention provides A method for evaluating low-temperature crack resistance of an asphalt mixture layer, comprising: A step of applying a tensile load to a specimen made of the asphalt mixture constituting the asphalt mixture layer at a predetermined test temperature to break the specimen, and acquiring a breaking strain and / or a breaking stress; Evaluating the low-temperature crack resistance of the asphalt mixture layer based on the obtained fracture strain and / or fracture stress; The present invention solves the above problems by providing a method comprising the steps of: Effect of the Invention

[0015] According to the tensile test method of one aspect of the present invention, it is possible to measure the stress-strain relationship of a specimen made of an asphalt mixture, and to measure the breaking strain and / or breaking stress simply and quickly. The breaking strain and / or breaking stress of a specimen made of an asphalt mixture at a predetermined test temperature can be advantageously used, in particular, to evaluate the low-temperature crack resistance of a pavement made of the asphalt mixture in cold regions. [Brief description of the drawings]

[0016] [Figure 1] 1A and 1B are diagrams showing the structure of an inner frame structure 100 that constitutes a form unit 10. (A) is a perspective view of the inner frame structure 100, (B) is a view of the inner frame structure 100 seen from above, (C) is a view of the inner frame structure 100 seen from a side, and (D) is a view of the inner frame structure 100 seen from below. [Diagram 2] 2 is a diagram showing the structure of an outer frame structure 200 that constitutes the form unit 10. FIG. [Diagram 3] 1A and 1B are diagrams showing a state in which three inner frame structures 100 are installed on an outer frame structure 200. (A) is a diagram seen from above, and (B) is a diagram seen from below. [Figure 4] FIG. 2 is a diagram showing the structure of a demolding machine 300. [Diagram 5] 1A and 1B are diagrams showing a process of removing a specimen from a form unit 10 using a demolding machine 300. (A) shows a state in which the jack is lowered, and (B) shows a state in which the jack is raised. [Figure 6] 1A is a diagram showing the dimensions of a specimen used in an experimental example, and B is a photograph of the specimen. Figures A and B show a front view, a side view, and a bottom view of the specimen. [Figure 7] 1 is a photograph showing a typical fracture mode of a test specimen in a tensile test. [Figure 8] 1A is a diagram and B is a photograph showing the state in which a test specimen is attached to a fixture of a tensile testing machine and a strain gauge is further attached. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] <1. Tensile test method> The tensile test method according to one aspect of the present invention will be described in more detail below.

[0018] A tensile test method according to one aspect of the present invention is a tensile test method for a specimen made of an asphalt mixture. An asphalt mixture is a mixture of aggregate, asphalt, filler, etc. in a predetermined mixing ratio, and is a paving material used for the surface layer or base layer of an asphalt pavement, and is sometimes called asphalt concrete or asphalt mixture. The asphalt mixture that can be used in the present invention may basically be any type as long as it contains aggregate and asphalt and is a mixture called an asphalt mixture in this technical field, and may be, for example, a room temperature asphalt mixture or an asphalt mixture containing modified asphalt. There is no particular limitation on the type of aggregate, and the aggregate may be, for example, a coarse aggregate, a fine aggregate, a recycled aggregate, etc.

[0019] There is also no particular limitation on the origin of the test specimen made of the asphalt mixture. For example, it may be cut out from an already constructed asphalt pavement, or it may be prepared for a tensile test.

[0020] In a preferred embodiment, the specimen used in the tensile test method according to one aspect of the present invention may be a rod-shaped specimen that includes a pair of fixed parts, a parallel part provided between the pair of fixed parts, and a pair of intermediate parts provided between the pair of fixed parts and the parallel part along the longitudinal direction of the specimen, i.e., the load axis direction of the tensile load, and is formed so that the cross-sectional areas of the parallel parts, intermediate parts, and fixed parts increase in that order. In other words, the specimen may be a rod-shaped specimen in which fixed parts are formed at both ends of the parallel parts in the longitudinal direction via intermediate parts, and is formed so that the cross-sectional areas of the parallel parts, intermediate parts, and fixed parts increase in that order. The side surfaces of the parallel parts are parallel to the load axis direction.

[0021] In a preferred embodiment, the cross-sectional area of ​​the parallel portion perpendicular to the load axis direction is preferably 60% or more and 95% or less, more preferably 70% or more and 90% or less, and even more preferably 75% or more and 85% or less, of the cross-sectional area of ​​the fixed portion perpendicular to the load axis direction.

[0022] According to the findings of the present inventors, by using a specimen characterized by the cross-sectional areas of the parallel portion, intermediate portion, and fixed portion as described above, when a tensile load is applied in the longitudinal direction of the specimen, the specimen can be broken more reliably at the parallel portion located in the center of the specimen, making it possible to obtain breaking strain, breaking stress, etc. that reflect the properties of the asphalt mixture that constitutes the specimen. Furthermore, a specimen having the above shape has sufficient strength for handling and is easy to handle.

[0023] Although there is no particular limitation on the cross-sectional shape of the specimen, in a preferred embodiment, the cross-sectional shape of the specimen in the longitudinal direction, i.e., perpendicular to the load axis direction, may be rectangular, more preferably square. That is, in a preferred embodiment, the parallel part of the specimen is rectangular prism-shaped, the intermediate part is rectangular pyramid-shaped, and the fixed part is rectangular prism-shaped.

[0024] In a preferred embodiment, the specimen preferably has a pair of flat side surfaces in the thickness direction perpendicular to the load axis direction. In other words, the specimen preferably has a uniform cross-sectional shape in the thickness direction perpendicular to the load axis direction. When a specimen having a pair of flat side surfaces in the thickness direction is used, the strain of the specimen during the tensile test can be accurately measured by attaching strain gauges to the pair of side surfaces, preferably at positions corresponding to the parallel parts. The number of strain gauges may be one, but is preferably two or more. When the specimen has two strain gauges, for example, one strain gauge may be attached to each of the pair of side surfaces in the thickness direction perpendicular to the load axis direction of the specimen.

[0025] There is no particular limit to the dimensions of the specimen, and a person skilled in the art can adopt appropriate dimensions depending on the dimensions of the jigs of the tensile tester. As an example, the total length of the specimen may be, for example, 100 mm to 400 mm, preferably 110 mm to 300 mm, more preferably 120 mm to 250 mm, and even more preferably 140 mm to 200 mm. The length of the parallel part may be, for example, 5 mm to 50 mm, preferably 10 mm to 40 mm, and more preferably 15 mm to 30 mm. If the length of the parallel part is too short, there is a risk that the parallel part will not break. On the other hand, the length of the fixing part may be, for example, 10 mm to 50 mm, preferably 15 mm to 45 mm, and more preferably 20 mm to 40 mm. If the length of the fixing part is too short, the specimen cannot be sufficiently fixed, and there is a risk that the specimen will fall off during the tensile test without breaking. The length of the intermediate portion may be appropriately set depending on the length and cross-sectional area of ​​the parallel portion and the fixed portion, and may be, for example, 10 mm to 100 mm, preferably 20 mm to 80 mm, and more preferably 30 mm to 60 mm. If the length of the intermediate portion is too short, stress may be concentrated in the intermediate portion, and there is a risk that the parallel portion will not break.

[0026] In the tensile test, a tensile load is applied to the above-mentioned specimen made of the asphalt mixture at a predetermined test temperature, and the strain and / or stress are measured. A commercially available tensile tester, for example, a uniaxial tensile tester, can be used for the tensile test. The tensile load is preferably applied in the longitudinal direction of the above-mentioned specimen.

[0027] When applying a tensile load in the longitudinal direction of the specimen, a pair of fixing parts located at the ends of the specimen are fixed to an appropriate fixing device provided in the tensile tester. There is no particular limitation on the fixing device for fixing the specimen or the specific method for fixing the fixing part of the specimen to the fixing device, and a person skilled in the art can adopt an appropriate fixing device and fixing method, but for example, the fixing device is preferably a fixing device having a bottom shape substantially the same as the cross-sectional shape in a plane perpendicular to the longitudinal direction of the fixing part of the specimen, and having a depth of at least 5 mm or more, preferably 10 mm or more, more preferably 15 mm or more, and even more preferably 20 mm or more, and the fixing method is preferably fixing with an adhesive. By fixing the specimen using an adhesive, it is possible to reduce the possibility that stress will concentrate on the fixing part and break at the fixing part. There is no particular limitation on the type of adhesive that can be used to fix the specimen, but for example, an epoxy resin-based adhesive can be used.

[0028] To apply a tensile load in the longitudinal direction of the specimen, the specimen may be pulled in the longitudinal direction while the fixed portion of the specimen is fixed. The pulling speed when applying a tensile load in the longitudinal direction of the specimen may be, for example, 0.01 mm / min to 100 mm / min, 0.1 mm / min to 10 mm / min, or 0.5 mm / min to 5 mm / min.

[0029] There is no particular limitation on the test temperature at which the tensile test method according to one aspect of the present invention is carried out, and the tensile test can be carried out at an appropriate test temperature. In a preferred embodiment, the test temperature may be a test temperature assumed for cold regions, for example, 4°C or lower, more preferably 0°C or lower, even more preferably -5°C or lower, and even more preferably -10°C or lower. The stress relaxation mechanism due to the viscosity of the asphalt constituting the asphalt mixture is lost in the low temperature region, and as a result, the molded product of the asphalt mixture undergoes brittle fracture due to tension. According to the findings of the present inventors, cracks in asphalt pavement in cold regions, so-called low-temperature cracks, are thought to be caused by tensile stress generated in the asphalt mixture layer in the low temperature region as described above. The test temperature can be appropriately adjusted, for example, by using a tensile tester equipped with a thermostatic bath.

[0030] <2. Evaluation method for low-temperature crack resistance> A method for evaluating the low-temperature crack resistance of an asphalt mixture layer according to one aspect of the present invention includes: A step of applying a tensile load to a specimen made of the asphalt mixture constituting the asphalt mixture layer at a predetermined test temperature to break the specimen, and acquiring a breaking strain and / or a breaking stress; Evaluating the low-temperature crack resistance of the asphalt mixture layer based on the obtained fracture strain and / or fracture stress; Hereinafter, the method for evaluating low-temperature crack resistance according to one aspect of the present invention will be described in more detail for each step.

[0031] <2.1. Step of obtaining breaking strain and / or breaking stress> This is a process in which a molded product made of an asphalt mixture constituting the asphalt mixture layer to be evaluated for low-temperature crack resistance is used as a specimen, and the breaking strain and / or breaking stress are obtained by the above-mentioned tensile test method. The tensile test method and the specimens used in the tensile test method have already been explained, so their explanation will be omitted.

[0032] The test specimen made of the asphalt mixture constituting the asphalt mixture layer to be evaluated for low-temperature crack resistance does not necessarily mean a test specimen taken from the pavement site to be evaluated for low-temperature crack resistance, but may be a test specimen made from an asphalt mixture having the same composition as the asphalt mixture that has been or will be constructed at the pavement site to be evaluated. When a new test specimen is made from an asphalt mixture having the same composition as the asphalt mixture that has been or will be constructed at the pavement site to be evaluated, it is convenient because the test specimen can be easily made using a formwork unit described later. On the other hand, using a test specimen taken from the pavement site is advantageous because test results that more accurately reflect the deterioration of the asphalt pavement at the site can be obtained.

[0033] In this specification, break means that a specimen breaks into two or more parts when a tensile load is applied in the longitudinal direction of the specimen. The stress when the specimen breaks is called the breaking stress, and the strain at this time is called the breaking strain. The breaking strain and / or breaking stress can be measured by applying a tensile load to the specimen until it breaks.

[0034] <2.2. Process for evaluating low-temperature crack resistance> This is a step of evaluating the low-temperature crack resistance of the asphalt mixture layer based on the fracture strain and / or fracture stress obtained in the above-mentioned step. When evaluating low-temperature crack resistance, in addition to predicting whether or not low-temperature cracks will occur when the asphalt mixture layer to be evaluated is used in a specified environment, it also includes evaluating the resistance to low-temperature cracks in comparison with a specified standard. In other words, unless otherwise specified, the evaluation of low-temperature crack resistance may include both absolute and relative evaluation of low-temperature crack resistance.

[0035] In a preferred embodiment, the low-temperature crack resistance of the asphalt mixture layer can be evaluated by comparing the fracture strain and / or fracture stress obtained in the above-mentioned process with an estimated value of the strain and / or stress predicted to occur in the asphalt mixture layer at the site where the asphalt mixture layer is used. Here, the estimated value of the strain and / or stress predicted to occur in the asphalt mixture layer at the site where the asphalt mixture layer is used can be an estimated value of the strain and / or stress predicted to occur in the asphalt mixture layer due to a temperature change at the site where the asphalt mixture layer is used.

[0036] There are no particular limitations on the specific method for estimating the strain and / or stress predicted to occur in the asphalt mixture layer due to temperature changes at the site where the asphalt mixture layer is used, but the strain predicted to occur in the asphalt mixture layer at each site can be estimated, for example, based on the amount of temperature change per day in the asphalt mixture layer at the site and the linear expansion coefficient of the asphalt mixture layer, using the following formula.

[0037]

number

[0038] In the above formula, εt is the estimated strain, α is the linear expansion coefficient of the asphalt mixture layer (unit: 1 / ℃), and Δt is the temperature change of the asphalt mixture layer per day (unit: ℃). The linear expansion coefficient of the asphalt mixture layer may be confirmed experimentally or a literature value may be used.

[0039] On the other hand, the stress generated in the asphalt mixture layer at each site can be estimated, for example, based on the temperature change of the asphalt mixture layer per day at the site, the linear expansion coefficient of the asphalt mixture layer, and the elastic modulus of the asphalt mixture layer, using the following formula.

[0040]

number

[0041] In the above formula, σt is the estimated stress value, E is the elastic modulus of the asphalt mixture layer (unit: N / mm 2 ) The elastic modulus of the asphalt mixture layer may be experimentally confirmed or a literature value may be used. The elastic modulus of the asphalt mixture layer may be measured, for example, by the tensile test method according to one aspect of the present invention.

[0042] The temperature change amount of the asphalt mixture layer per day means the difference between the maximum temperature and the minimum temperature of the asphalt mixture layer in a day. More specifically, for example, when the asphalt mixture layer is a surface layer, the difference between the maximum road surface temperature and the minimum road surface temperature in a day can be used as the temperature change amount of the asphalt mixture layer per day. The temperature change amount of the asphalt mixture layer per day does not necessarily have to be an actual measured value, and may be an estimated value. The temperature change amount of the asphalt mixture layer per day may be, for example, an estimated value predicted from past road surface temperature data or temperature data of the asphalt mixture layer, or an estimated value predicted from past air temperature data. Since it is known that the air temperature and the temperature of the asphalt mixture layer are correlated, a person skilled in the art can estimate the temperature of the asphalt mixture layer based on air temperature data, etc.

[0043] There is no particular limitation to the specific evaluation method of low-temperature crack resistance, but for example, the magnitude relationship between the estimated value of strain and / or stress obtained in the above-mentioned process and the breaking strain and / or breaking stress at a predetermined test temperature obtained by a tensile test may be compared. Although this is only one example, if the estimated value of strain and / or stress predicted to occur at the site in the above-mentioned process exceeds the breaking strain and / or breaking stress at a predetermined test temperature obtained by a tensile test, it may be evaluated that the asphalt mixture layer will break or is likely to break. In addition, when comparing the magnitude relationship between the estimated value of strain and / or stress obtained in the above-mentioned process and the breaking strain and / or breaking stress at a predetermined test temperature obtained by a tensile test, a predetermined coefficient considering fatigue, aging, etc. of the asphalt mixture layer may be taken into consideration. This provides the advantage of being able to evaluate the low-temperature crack resistance for medium to long periods, such as several years or decades. As the predetermined coefficient taking into consideration fatigue, deterioration over time, etc. of the asphalt mixture layer, an appropriate coefficient can be used depending on the performance required for the asphalt pavement at each site.

[0044] As the predetermined test temperature, any appropriate test temperature can be used, but it is preferable that the test temperature is near the minimum temperature of the asphalt mixture layer on the site in one day, and more preferably, for example, it may be the minimum temperature of the asphalt mixture layer on the site in one day ±5°C, ±4°C, ±3°C, ±2°C, ±1°C, and even more preferably, it may be the minimum temperature of the asphalt mixture layer on the site in one day. Note that, as mentioned above, the minimum temperature of the asphalt mixture layer on one day does not necessarily have to be an actual measured value, and may be an estimated value.

[0045] In the method for evaluating low-temperature crack resistance according to one aspect of the present invention, the asphalt mixture layer to be evaluated may be a surface layer or a base layer, but is preferably a surface layer. The surface layer means the surface or uppermost layer of an asphalt pavement.

[0046] <3. Formwork unit> Next, a form unit according to one aspect of the present invention will be described. The form unit according to one aspect of the present invention is a form unit for preparing a specimen made of an asphalt mixture, and includes an inner frame structure and an outer frame structure.

[0047] The inner frame structure is formed by combining an inner frame bottom member and an inner frame side member, has an internal space surrounded by the inner frame bottom member and the inner frame side member, and has a convex portion on the lower surface of the inner frame bottom member. Note that the lower surface of the inner frame bottom member refers to the surface opposite to the surface to which the inner frame side member is attached and where the internal space is formed.

[0048] The top surface of the inner frame structure formed by combining the inner frame bottom member and the inner frame side member, i.e., the surface facing the inner frame bottom member, is open so that it can be filled with an asphalt mixture. In other words, the internal space surrounded by the inner frame bottom member and the inner frame side member has a box-like shape with an open top.

[0049] The asphalt mixture to be filled into the inner frame structure is filled into the internal space surrounded by the inner frame bottom member and the inner frame side member. The asphalt mixture filled into the internal space is compacted by an appropriate compaction means and formed into the shape of the internal space. In other words, the internal space in the inner frame structure is the part that serves as the mold for the specimen made of the asphalt mixture.

[0050] Since the inner frame structure is constructed by combining the inner frame bottom member and the inner frame side member, it can be disassembled into the inner frame bottom member and the inner frame side member. Even after the asphalt mixture is compacted, the compacted asphalt mixture can be easily removed by disassembling the inner frame structure into the inner frame bottom member and the inner frame side member. There is no particular limit to the number of inner frame side members, but for example, it is preferable that the number is 2 or more or 4 or more, and typically 4. When the inner frame side members are 2 or more or 4 or more, there is an advantage that the disassembly of the inner frame structure is further facilitated and the compacted asphalt mixture can be more easily removed. In addition, when the inner frame structure includes four inner frame side members, the four inner frame structures may include a pair of opposing side members for forming the side shape of the specimen and a pair of opposing side members for forming the upper and lower end face shapes of the specimen, as shown in the experimental example described later.

[0051] The inner frame side members may have a height such that the depth of the internal space formed by the inner frame bottom member and the inner frame side member is equal to or greater than the thickness of the specimen to be obtained, but it is preferable that the depth of the internal space is greater than the thickness of the specimen to be obtained. If the depth of the internal space formed by the inner frame bottom member and the inner frame side member is greater than the thickness of the specimen to be obtained, the thickness of the molded product of the asphalt mixture obtained by filling the internal space with the asphalt mixture, compacting it, and removing it will be greater than the thickness of the specimen to be obtained. In this case, there is an advantage in that the excess thickness of the molded product can be cut off to more accurately adjust the thickness of the specimen.

[0052] A convex portion is provided on the lower surface of the inner frame bottom member constituting the inner frame structure. This convex portion is intended to fit into a through hole provided in the outer frame bottom member constituting the outer frame structure described below, and to stably install the inner frame structure on the outer frame structure. The shape, dimensions, number, etc. of the convex portion provided on the lower surface of the inner frame bottom member and the through hole that fits into the convex portion are not particularly limited as long as the inner frame structure can be stably installed on the outer frame structure, and a person skilled in the art can determine appropriate shapes, dimensions, and numbers.

[0053] On the other hand, the outer frame structure is an outer frame structure formed by combining an outer frame bottom member and an outer frame side member, and is capable of accommodating one or more of the inner frame structures in an internal space surrounded by the outer frame bottom member and the outer frame side member, and the outer frame bottom member is provided with one or more through holes that engage with the convex portions of the inner frame structure.

[0054] The upper surface of the outer frame structure formed by combining the outer frame bottom member and the outer frame side member, i.e., the surface facing the outer frame bottom member, is open, so that the inner frame structure can be installed from the upper surface. In other words, the internal space surrounded by the outer frame bottom member and the outer frame side member has a box-like shape with an open upper surface. The internal space surrounded by the outer frame bottom member and the outer frame side member can accommodate the inner frame structure. Here, being able to accommodate the inner frame structure means that the inner frame structure can be accommodated in a state in which the inner frame bottom member and the inner frame side member are combined, that is, the inner frame structure fits into the internal space surrounded by the outer frame bottom member and the outer frame side member in a state in which the inner frame bottom member and the inner frame side member are combined.

[0055] Since the outer frame structure is constructed by combining the outer frame bottom member and the outer frame side member, it can be disassembled into the outer frame bottom member and the outer frame side member. Even after the asphalt mixture is compacted, the outer frame structure can be disassembled into the outer frame bottom member and the outer frame side member, which has the advantage of making it easy to carry, clean, and the like. There is no particular limit to the number of outer frame side members, but for example, it is preferable that the number is 2 or more or 4 or more, and typically 4. When the outer frame side members are 2 or more or 4 or more, there is an advantage that the outer frame structure can be disassembled even more easily and the compacted asphalt mixture can be removed more easily. In addition, when the outer frame structure includes four outer frame side members, the four outer frame structures may include a pair of side members facing each other in the width direction of the outer frame structure and a pair of side members facing each other in the depth direction of the outer frame structure.

[0056] In addition, a through hole is provided on the lower surface of the outer frame bottom member constituting the outer frame structure. This through hole is intended to fit with the convex portion provided on the inner frame bottom member constituting the inner frame structure described above, and to stably install the inner frame structure on the outer frame structure. It is preferable that the through hole provided on the lower surface of the outer frame bottom member and the convex portion that fits with the through hole have approximately the same shape. There is no particular limit to the number of inner frame structures that can be installed on the outer frame structure, and an appropriate number of inner frame structures may be installed, but the number of inner frame structures that can be installed on the outer frame structure may be, for example, 1 or more, 2 or more, or 3 or more. When the number of inner frame structures that can be installed on the outer frame structure increases, the size of the outer frame bottom member and the number of through holes provided on the outer frame bottom member also increase accordingly.

[0057] A procedure for preparing a specimen made of an asphalt mixture using a form unit according to one aspect of the present invention will be described. First, the inner frame bottom member and the inner frame side member are combined to assemble the inner frame structure, and the outer frame bottom member and the outer frame side member are combined to assemble the outer frame structure. The convex portion provided on the lower surface of the inner frame bottom member of the assembled inner frame structure is fitted into the through hole provided in the outer frame bottom member of the outer frame structure, and the inner frame structure is installed in the outer frame structure. In this state, the form unit, more specifically, the outer frame structure and the inner frame structure installed in the outer frame structure, are filled with an asphalt mixture. After filling the form unit with the asphalt mixture, the asphalt mixture may be compacted using an appropriate means. There is no particular limitation on the method of compacting the asphalt mixture, and it may be compacted mechanically using a compacting machine or manually using an appropriate tool.

[0058] Here, in the formwork unit according to one aspect of the present invention, the inner frame structure is attached to the outer frame structure in a state in which the convex portion provided on the lower surface of the inner frame bottom member is fitted into the through hole provided in the outer frame bottom member of the outer frame structure, so that after compaction of the asphalt mixture layer, the convex portion provided on the inner frame bottom member of the inner frame structure is exposed on the lower surface of the outer frame structure. Therefore, when the formwork unit according to one aspect of the present invention is used, even after the asphalt mixture is compacted, the inner frame structure can be easily removed from the outer frame structure by pressing the convex portion provided on the inner frame bottom member of the inner frame structure from the lower surface of the outer frame bottom member. There is no particular limitation on the specific method of pressing the convex portion, but for example, it may be pushed up using a jack.

[0059] <4. Test specimen preparation equipment> In addition, in one aspect, the present invention provides a method for producing a liquid crystal display comprising the steps of: a first mounting table on which the form unit is mounted; a fixing means for fixing the form unit placed on the first placement table; A second platform is provided, the second platform being located below the first platform and capable of supporting a jack below the fixed form unit; The first mounting table provides a specimen preparation device characterized in that, when the formwork unit is fixed by the fixing means, it has a jack insertion hole at a position corresponding to the through hole provided in the outer frame structure that constitutes the fixed formwork unit.

[0060] As described above, when preparing a test specimen made of an asphalt mixture using the formwork unit according to one aspect of the present invention, the inner frame structure is attached to the outer frame structure with the convex portion provided on the underside of the inner frame bottom member being fitted into the through hole provided in the outer frame bottom member of the outer frame structure, and at this time, the convex portion of the inner frame structure is exposed on the underside of the outer frame structure. Therefore, according to the above-mentioned specimen preparation device which comprises a first mounting table on which the form unit is placed, a fixing means for fixing the form unit placed on the first mounting table, and a second mounting table located below the first mounting table and on which a jack can be placed below the fixed form unit, and the first mounting table has a jack insertion hole at a position corresponding to the through hole provided in the outer frame structure that constitutes the fixed form unit when the form unit is fixed by the fixing means, it is possible to obtain the advantage that after the asphalt mixture is compacted using the form unit, it becomes extremely easy to remove the inner frame structure using a jack.

[0061] <5. Experimental Example> The present invention will be described in more detail below based on experimental examples, but it goes without saying that the present invention is not limited to these experimental examples.

[0062] <5.1. Formwork unit> First, a description will be given of the form unit 10 used in this experiment. The form unit 10 is composed of three inner frame structures 100 and one outer frame structure 200 (FIG. 3).

[0063] FIG. 1 shows only the inner frame structure 100 constituting the form unit 10. As shown in FIG. 1, the inner frame structure 100 is configured by connecting an inner frame bottom member 101 and four inner frame side members 102-105 to each other via connecting members 106-109, and an internal space a is formed by the inner frame bottom member 101 and the four inner frame side members 102-10. Of the four inner frame side members, the inner frame side members 103 and 105 are side members for forming the side shape of the specimen to be produced. In this example, the inner frame side members 103 and 105 have a flat bottom surface, and are provided with a central portion parallel to the bottom surface and end portions parallel to the bottom surface via intermediate portions at both ends of the central portion, and are formed so that the thickness decreases in the order of the central portion, intermediate portion, and end portions. On the other hand, the pair of inner frame side members 102 and 104 are side members for forming the upper and lower end face shapes of the specimen to be fabricated, and in this example, the side faces on the inner space a side are formed flat. Also, a convex portion 110 is provided on the lower face of the inner frame bottom member.

[0064] Meanwhile, FIG. 2 shows only the outer frame structure 200 constituting the form unit 10. As shown in FIG. 2, the outer frame structure 200 is configured by combining an outer frame bottom surface member 201 and four outer frame side surface members 202 to 205, and further includes handles 206 and 207. The outer frame bottom surface member 201 and the four outer frame side surface members 202 to 205 form an internal space b, in which the inner frame structure 100 is housed. In this example, the outer frame structure 200 is configured so that three inner frame structures 100 can be installed. That is, the outer frame bottom surface member 201 of the outer frame structure 200 is formed with three mounting portions c for mounting the inner frame structure 100, and the mounting portions c are formed in approximately the same shape as the inner frame bottom surface member 101. In addition, each mounting portion c is provided with a through hole d having approximately the same shape as the protrusion 110. Six positioning pins e are provided around each of the mounting portions c to facilitate mounting of the inner frame structure 100 thereon.

[0065] FIG. 3 shows the formwork unit 10 in a state where three inner frame structures 100 are installed on the outer frame structure 200. In FIG. 3, the inner frame structure 100 is attached to the outer frame structure 200 with the lower surface of the inner frame bottom member 101 fitted into the mounting portion c and the protruding portion 110 provided on the lower surface of the inner frame bottom member 101 fitted into the through hole d, so that the inner frame structure 100 is stably installed on the outer frame structure 200. FIG. 3b shows a view of the formwork unit 10 at this time as seen from below. As shown in FIG. 3b, the protruding portion 110 of the inner structure 100 is exposed on the lower surface of the outer frame bottom member 201 of the outer frame structure 200. Thus, in the formwork unit 10 of this embodiment, the convex portion 110 of the inner structure 100 is exposed on the underside of the outer frame bottom member 201 of the outer frame structure 200, so that the inner structure 100 can be easily removed by pushing out the convex portion 110 even after the asphalt mixture has been compacted.

[0066] 4 shows the demolding machine 300. As shown in FIG. 4, the demolding machine 300 includes a first mounting table 301 for mounting the form unit 10, and a fixing tool 302 and a nut 303 as fixing means for fixing the form unit 10 mounted on the mounting table 301. A second mounting table 304 is provided below the mounting table 301, and by mounting a jack on the mounting table 304, the jack can be mounted below the form unit 10 mounted on the mounting table 301 and fixed by the fixing tool 302 and the nut 303. In addition, three jack insertion holes f are provided on the mounting table 301 at positions corresponding to three through holes d provided in the outer frame structure 200 constituting the fixed form unit 10 in a state in which the form unit 10 is fixed by the fixing tool 302 and the nut 303. In this example, the jack insertion hole f is a circular hole that is large enough for the jack to pass through.

[0067] <5.2. Preparation of test specimen> Specimen A was made from a dense-graded asphalt mixture containing polymer-modified asphalt (II type) as the asphalt, specimen B was made from a porous asphalt mixture containing polymer-modified asphalt (H type) as the asphalt, and specimen C was made from a dense-graded asphalt mixture containing polymer-modified asphalt (H type) as the asphalt. The asphalt content of each specimen was 5.5% for specimen A, 4.9% for specimen B, and 5.6% for specimen C.

[0068] Specimens A to C were prepared using the above-mentioned form unit 10. Specifically, in a state where three inner structures 100 were installed on the outer frame structure 200 of the form unit 10, the form unit 10 was filled with an asphalt mixture, lightly compacted with a tamper, and then compacted with a rolling machine. Thereafter, the inner structure 100 was removed from the form unit 10 using a demolding machine 300. Specifically, as shown in FIG. 5, the form unit 10 was placed on a mounting table 301 of the demolding machine 300, and the mounted form unit 10 was fixed on the mounting table 301 using a fixing tool 302 and a nut 303. In this state, the convex portion 110 of the inner frame structure 100 was pushed up from below using a jack 305 mounted on the mounting table 304, and the inner structure 100 was removed from the form unit 10. The inner structure 100 thus taken out was disassembled into the inner bottom member 101 and the inner side members 102 to 105 to take out the molded asphalt mixture. The end face of the obtained asphalt mixture was appropriately cut so that the thickness of the test specimen was a predetermined thickness (50 mm in this example), and a test specimen was obtained.

[0069] The shape of the specimen 400 obtained as described above is shown in Fig. 6. As shown in Fig. 6, the specimen 400 is generally rod-shaped, with a parallel portion 401 in the center in the longitudinal direction, intermediate portions 402 having a larger cross-sectional area than the parallel portion 401 at both ends in the longitudinal direction of the parallel portion 401, and fixed portions 403 having an even larger cross-sectional area than the intermediate portion 402 at both ends in the longitudinal direction of the intermediate portion 402. The dimensions of the specimen 400 are as shown in Fig. 6, with a total length of 160 mm, a length of the parallel portion 401 of 20 mm, a length of the intermediate portion 402 of 40 mm, a length of the fixed portion 403 of 50 mm, a width of 50 mm at the fixed portion and 40 mm at the parallel portion, and a thickness in the depth direction of the entire specimen 400 of 50 mm. The cross section of specimen 400 perpendicular to the longitudinal direction is rectangular, with dimensions of 50 mm x 50 mm at the fixed portion and 40 mm x 50 mm at the parallel portion in the center of the specimen. That is, the cross-sectional area of ​​the parallel portion is 80% of the cross-sectional area of ​​the fixed portion. Note that the shape of specimen 400 is merely an example of the shape of a specimen that can be used in the method according to one aspect of the present invention, and it goes without saying that specimens of other shapes may also be used.

[0070] FIG. 7A shows a typical fracture mode when a tensile load is applied in the longitudinal direction of the specimen 400 to break the specimen. As shown in FIG. 7A, when a rod-shaped specimen 400 is used, which is provided with a pair of fixing parts, a parallel part provided between the pair of fixing parts, and a pair of intermediate parts provided between the pair of fixing parts and the parallel parts, and is formed so that the cross-sectional area of ​​the cross section perpendicular to the load axis direction, i.e., the longitudinal direction of the specimen, increases in the order of the parallel part, the intermediate part, and the fixing part, fracture occurs in the parallel part located at the center of the specimen, so that a stress-strain curve reflecting the characteristics of the asphalt mixture constituting the specimen 400 can be drawn by a tensile test. On the other hand, FIG. 7B shows a comparison of typical fracture modes when a tensile load is applied in the longitudinal direction of a rectangular parallelepiped specimen to break the specimen. As shown in Figure 7B, when a rectangular specimen was used, the stress applied to the specimen was uneven, and destruction almost always occurred near the jig that fixed the specimen. As a result, it was not easy to draw a stress-strain curve that reflected the characteristics of the asphalt mixture that made up the specimen.

[0071] <5.3. Tensile test> A uniaxial tensile test was performed on each of the specimens A to C obtained as described above using a uniaxial tensile tester (Instron Japan Co., Ltd. / Universal Material Testing Machine / ESPECCORT TG-4J). In order to measure the strain, as shown in FIG. 8, the fixing parts 403 at both ends of the specimens A to C were fixed to the fixtures of the tensile tester using an epoxy resin adhesive, and a total of two strain gauges (Tokyo Measuring Instruments Laboratory Co., Ltd. / Strain Gauge / TL-60-11-3LJQTA-F) were attached to the approximate center of a pair of flat side surfaces of each specimen, that is, at positions corresponding to the parallel parts. The test temperatures were -15°C and -20°C, and the specimens were cured in a thermostatic chamber for at least 5 hours before the tensile test was started. The tensile speed was 1 mm / min. The average values ​​of the fracture stress and fracture strain obtained from three independent tests on each of the specimens A to C are shown in Table 1.

[0072] [Table 1]

[0073] As shown in Table 1, the breaking stress of specimen A at -15°C was 5.81 MPa and the breaking strain was 297μ (= 297 × 10 -6 ), the fracture stress of specimen B is 3.40 MPa, and the fracture strain is 497 μ (= 497 × 10 -6 ), the fracture stress of specimen C was 5.91 MPa, and the fracture strain was 330 μ (= 330 × 10 -6 On the other hand, the breaking stress of specimen A at -20°C was 5.85 MPa and the breaking strain was 239μ (= 239 × 10 -6 ), the fracture stress of specimen B is 3.30 MPa, and the fracture strain is 412μ (= 412 × 10 -6 ), the fracture stress of specimen C is 5.45 MPa, and the fracture strain is 260μ (= 260 × 10 -6 ) was.

[0074] As described above, for each specimen, there was no significant difference between the breaking stress at -15°C and the breaking stress at the test temperature of -20°C, whereas there was a significant difference between the breaking strain at -15°C and the breaking strain at the test temperature of -20°C. The breaking stress is mainly affected by the adhesion between the aggregate and asphalt that constitute the asphalt mixture, and is therefore considered to be less susceptible to the effects of temperature. On the other hand, since the asphalt that constitutes the asphalt mixture has a lower ability to elongate at low temperatures, it is considered that the breaking strain of the asphalt mixture becomes smaller at lower test temperatures. The above results obtained by the tensile test according to one embodiment of the present invention reflect the characteristics of the asphalt mixture that constitutes the specimen, and demonstrate the usefulness of the tensile test according to one aspect of the present invention.

[0075] On the other hand, in order to evaluate the low-temperature crack resistance of specimens A to C when they are applied to a site in a cold region, the strain predicted to occur in the surface asphalt mixture layer at a site where an asphalt mixture with the same composition as specimens A to C is applied to the surface layer was estimated according to the following formula.

[0076]

number

[0077] Here, εt is the strain that occurs in the asphalt mixture layer due to temperature change, α is the linear expansion coefficient of the asphalt mixture layer (unit: 1 / ℃), and Δt is the change in road surface temperature per day (unit: ℃). The linear expansion coefficient α is set to 25×10 -6 (1 / ℃) was used (Doi Masahiko, Saruwatari Mamoru, "A Study on the Applicability of Buried Strain Gauges in Asphalt Mixtures", 57th Annual Academic Lecture Meeting of the Japan Society of Civil Engineers, September 2002). On the other hand, -13.4℃ was used as the daily road surface temperature change Δt, based on the fact that the road surface temperature at the site changed from 0.3℃ to -13.1℃.

[0078] Based on the above conditions, the strain predicted to occur at a site where asphalt mixtures of the same composition as specimens A to C are used is 335μ (=335×10 -6 ) was estimated.

[0079] Based on the daily road surface temperature change (Δt) and the linear expansion coefficient (α) of the asphalt mixture layer at the site where the asphalt mixture layer made of the same composition as the test specimen A is applied, the strain (εt) predicted to occur at the site is 335μ, whereas the fracture strain of the test specimen A at the test temperature (-15°C) close to the lowest temperature at the site, -13.1°C, was 297μ, which was smaller than 335μ. This result suggests that when the road surface at the site changes in temperature from 0.1°C to -13.1°C in winter, the asphalt mixture layer made of the test specimen A forming the surface layer of the road surface will not be able to withstand the strain caused by the temperature change and will fracture. In fact, it has been reported that low-temperature cracks occurred within one year after construction at the site where the test specimen A was applied. Thus, the tensile test method according to one aspect of the present invention can be advantageously used to evaluate the low-temperature crack resistance of the asphalt mixture layer.

[0080] Based on the daily road surface temperature change (Δt) and the linear expansion coefficient (α) of the asphalt mixture layer at the site where the asphalt mixture layer made of the same composition as that of the test specimen C is applied, the strain (εt) predicted to occur at the site is 335μ, whereas the fracture strain of the test specimen C at the test temperature (-15°C) close to the lowest temperature at the site, -13.1°C, was 330μ, which was smaller than 335μ. This result suggests that when the road surface at the site changes in temperature from 0.1°C to -13.1°C in winter, the asphalt mixture layer made of the test specimen C forming the surface layer of the road surface will not be able to withstand the strain caused by the temperature change and will fracture. In fact, it has been reported that low-temperature cracks occurred within one year after construction at the site where the test specimen C was applied. Thus, the tensile test method according to one aspect of the present invention can be advantageously used to evaluate the low-temperature crack resistance of the asphalt mixture layer.

[0081] On the other hand, the strain (εt) predicted to occur at the site where an asphalt mixture layer made of an asphalt mixture having the same composition as that of specimen B is applied based on the change in road surface temperature per day (Δt) and the linear expansion coefficient (α) of the asphalt mixture layer is 335μ, whereas the fracture strain of specimen B at a test temperature (-15°C) close to the lowest temperature at the site, -13.1°C, was 497μ, which was smaller than 335μ. This result suggests that when the road surface at the site changes in temperature from 0.1°C to -13.1°C in winter, the asphalt mixture layer made of specimen B forming the surface layer of the road surface is less likely to fracture due to the strain caused by the temperature change, compared to specimen A and specimen C. Thus, the tensile test method according to one aspect of the present invention can be advantageously used to compare the low-temperature crack resistance of asphalt mixture layers made of various asphalt mixtures.

[0082] It has been reported that at a site where an asphalt mixture layer made of an asphalt mixture having the same composition as that of specimen B was applied to the surface layer, and an asphalt mixture layer made of an asphalt mixture having the same composition as that of specimen A or C was applied to the base layer below the surface layer, cracks in the pavement occurred within one year after construction, and these cracks are assumed to be reflection cracks resulting from cracks in the base layer made of an asphalt mixture having the same composition as that of specimen A or C. In this way, the tensile test method according to one aspect of the present invention can be advantageously used to predict crack behavior not only in the surface layer but also in the base layer. [Industrial Applicability]

[0083] According to the present invention, it is possible to easily carry out tensile tests on specimens made of asphalt mixtures. Furthermore, according to the method for evaluating low-temperature crack resistance according to one aspect of the present invention, it is possible to predict the occurrence of low-temperature cracks in cold regions in advance, and to efficiently select and design asphalt mixtures suitable for cold regions. Thus, the present invention has great industrial applicability.

Claims

1. A tensile test method for obtaining strain and / or stress by applying a tensile load to a specimen made of an asphalt mixture, comprising: The method is characterized in that the specimen is a rod-shaped specimen having, along the load axis direction of the tensile load, a pair of fixed portions, a parallel portion provided between the pair of fixed portions, and a pair of intermediate portions provided between the pair of fixed portions and the parallel portions, and is formed so that the cross-sectional areas of the cross sections perpendicular to the load axis direction increase in the order of the parallel portions, the intermediate portions, and the fixed portions.

2. 2. The method according to claim 1, wherein the cross-sectional area of ​​the parallel portion perpendicular to the load axis direction is 70% or more and 90% or less of the cross-sectional area of ​​the fixed portion perpendicular to the load axis direction.

3. The method according to claim 1 or 2, characterized in that a pair of side surfaces in the thickness direction perpendicular to the load axis direction in the test specimen are both flat.

4. The method according to claim 3, characterized in that a strain gauge is attached to at least one of the pair of side surfaces in the thickness direction of the specimen perpendicular to the load axis direction.

5. A method for evaluating low-temperature crack resistance of an asphalt mixture layer, comprising: A step of applying a tensile load to a specimen made of the asphalt mixture constituting the asphalt mixture layer at a predetermined test temperature to break the specimen and obtain the breaking strain and / or breaking stress; Evaluating the low-temperature crack resistance of the asphalt mixture layer based on the acquired fracture strain and / or fracture stress; The method includes:

6. In the step of evaluating the low-temperature crack resistance of an asphalt mixture layer, The method according to claim 5, characterized in that the obtained fracture strain and / or fracture stress are compared with an estimated value of a strain and / or stress predicted to occur in the asphalt mixture layer due to temperature changes at a site where the asphalt mixture layer is used, thereby evaluating the low-temperature crack resistance of the asphalt mixture layer.

7. 7. The method of claim 6, wherein the estimate of strain is estimated based on a daily temperature change at the site where the asphalt mix layer is in service and a coefficient of linear expansion of the asphalt mix layer.

8. 7. The method of claim 6, wherein the estimated stress is estimated based on a daily temperature change at the site where the asphalt mixture layer is in service, a coefficient of linear expansion of the asphalt mixture layer, and a modulus of elasticity of the asphalt mixture layer.

9. The method according to any one of claims 5 to 8, characterized in that the specimen is a rod-shaped specimen having, along the load axis direction of the tensile load, a pair of fixed portions, a parallel portion provided between the pair of fixed portions, and a pair of intermediate portions provided between the pair of fixed portions and the parallel portions, and is formed so that the cross-sectional areas of the cross sections perpendicular to the load axis direction increase in the order of the parallel portions, the intermediate portions, and the fixed portions.

10. 10. The method according to claim 9, wherein the cross-sectional area of ​​the parallel portion perpendicular to the load axis direction is 70% or more and 90% or less of the cross-sectional area of ​​the fixed portion perpendicular to the load axis direction.

11. The method according to claim 10, wherein a pair of side surfaces in the thickness direction perpendicular to the load axis direction of the specimen are both flat.

12. The method according to claim 11, characterized in that a strain gauge is attached to at least one of the pair of side surfaces in the thickness direction of the specimen perpendicular to the load axis direction.

13. A formwork unit for preparing a specimen made of an asphalt mixture, An inner frame structure formed by combining an inner frame bottom member and an inner frame side member, the inner frame structure having an internal space surrounded by the inner frame bottom member and the inner frame side member, the inner frame structure having a convex portion on a lower surface of the inner frame bottom member; an outer frame structure formed by combining an outer frame bottom member and an outer frame side member, capable of accommodating one or more of the inner frame structures in an internal space surrounded by the outer frame bottom member and the outer frame side member, the outer frame bottom member having one or more through holes that engage with the protrusions of the inner frame structure; A formwork unit having the above structure.

14. A formwork unit according to claim 13; a first mounting table on which the form unit is mounted; a fixing means for fixing the form unit placed on the first placement table; A second platform is provided, the second platform being located below the first platform and capable of supporting a jack below the fixed form unit. The first mounting table is characterized in that, when the formwork unit is fixed by the fixing means, it has a jack insertion hole at a position corresponding to the through hole provided in the outer frame structure that constitutes the fixed formwork unit.

Citation Information

Cited By

  • Asphalt extensibility detection device for highway construction

    CN120293725A